Novel imaging finding and novel mutation in an infant with molybdenum cofactor deficiency: a mimicker of hypoxic ischaemic encephalopathy - Yoganathan, Sangeetha; Sudhakar, Sniya Valsa; Thomas, Maya Mary; Dutta, Atanu Kumar; Danda, Sumita; Chandran, Mahalakshmi (Iranian Journal of Child Neurology, 2018)
Molybdenum cofactor deficiency is a rare metabolic disorder with neonatal onset seizures, developmental delay, microcephaly and spasticity. In this report, we describe a three-month-old infant presented with neonatal onset, poorly controlled seizures, developmental delay, microcephaly, spastic quadriparesis and visual insufficiency. Magnetic resonance imaging of brain had shown cystic encephalomalacia involving bilateral parieto-occipital lobe, and elevated lactate in magnetic resonance spectroscopy. Restricted diffusion noted along the corticospinal tract in our case is a novel imaging finding in molybdenum cofactor deficiency. Low serum uric acid and elevated urine sulphite excretion were observed. A novel homozygous mutation was detected in exon 4 of MOCS2 gene. Early infantile or neonatal onset seizures, developmental delay, microcephaly and cystic encephalomalacia in neuroimaging mimicking hypoxic ischaemic encephalopathy should raise the suspect for molybdenum cofactor deficiency. Screening of all neonates for urinary sulphite metabolites helps in early diagnosis and management. Early diagnosis and treatment with cyclic pyranopterin monophosphate could arrest the progression of this disease. More research is needed to explore further treatment options in this otherwise lethal disorder.